2014
DOI: 10.2478/s11686-014-0221-7
|View full text |Cite
|
Sign up to set email alerts
|

Toxocariasis and lung function: Relevance of a neglected infection in an urban landscape

Abstract: Toxocariasis has been highlighted as a potentially important neglected infection of poverty in developed countries that experience substantive health disparities such as the United States. An association between Toxocara infection and lung function, in concert with a relatively high prevalence of infection, may mark an important mechanism by which this infection could contribute significantly to the differential morbidity across different socioeconomic groups and landscapes. To assess the potential relevance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 17 publications
4
9
0
Order By: Relevance
“…Similar to the previous seroprevalence study utilizing data obtained over 20 years ago, we showed a persistent elevation in odds of antibody positivity in adults among minority ethnicity, male gender and low education level [ 17 ]. These findings overall mirror those found by Congdon et al demonstrating minority ethnicity and poverty were important drivers of higher levels of Toxocara antibody positivity [ 8 , 18 ]. Conversely, with non-Hispanic white as the reference, we found Hispanic and other race/multicultural ethnicities to have a higher risk of exposure than non-Hispanic Black.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar to the previous seroprevalence study utilizing data obtained over 20 years ago, we showed a persistent elevation in odds of antibody positivity in adults among minority ethnicity, male gender and low education level [ 17 ]. These findings overall mirror those found by Congdon et al demonstrating minority ethnicity and poverty were important drivers of higher levels of Toxocara antibody positivity [ 8 , 18 ]. Conversely, with non-Hispanic white as the reference, we found Hispanic and other race/multicultural ethnicities to have a higher risk of exposure than non-Hispanic Black.…”
Section: Discussionsupporting
confidence: 87%
“…For children, no difference was found in demographic data despite looking at multiple variables including age, gender, socioeconomic status and ethnicity. Additional factors that have previously been associated such as a diagnosis of asthma and eosinophilia were also not significantly different [ 8 , 34 ]. Interestingly, a protective effect of health insurance was noted.…”
Section: Discussionmentioning
confidence: 89%
“…[17,18] Covert toxocariasis may also represent an important environmental cause of asthma among disadvantaged American children. [19,20] Throughout the history of the National Health and Nutrition Examination Survey (NHANES), the prevalence of Toxocara within the United States population has varied, ranging from 5%-14% during analyses from 1988-1994 and 2011-2014. [11,21] In both studies, Toxocara seropositivity was disproportionately higher in persons from lower socioeconomic status communities, particularly in Hispanic, non-Hispanic black communities, and those with less than a high-school education.…”
Section: Introductionmentioning
confidence: 99%
“…Human toxocariasis (HT) is an infection caused primarily by the roundworm Toxocara canis and to a lesser extent by T. cati [1]. It is a zoonosis with a worldwide distribution including temperate regions, although greater prevalence rates are observed in tropical areas [2][3][4]. Human infection occurs after the accidental ingestion of food or soil contaminated with eggs of the parasite.…”
Section: Introductionmentioning
confidence: 99%